Evolution of sex differences in cooperation can be explained by trade-offs with dispersal - Capilla-Lasheras, Pablo; Bircher, Nina; Brown, Antony M.; Harrison, Xavier; Reed, Thomas; York, Jennifer E.; Cram, Dominic L.; Rutz, Christian; Walker, Lindsay; Naguib, Marc; Young, Andrew J. (PLOS Biology, 2024)
Why do the more philopatric sex tend to be more cooperative within family groups than the more dispersive sex? This study uses radio tracking of white-browed sparrow weavers to reveal that sex differences in cooperation can be attributable to sex differences in the direct costs of cooperation, arising from a trade-off between cooperation and dispersal.